Using Youtube as a Learning Tool for Basic Volleyball Techniques for Junior High School Students during Pandemic - Syaputra, Ijlal Dhea; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (LPPM Universitas Jenderal Achmad Yani, 2021)
The COVID-19 pandemic has had a major impact on education in Indonesia. Various efforts were made to attract students' interest in learning, one of the efforts made by the teacher was a learning video with the aim that students were able to understand the lesson well. The purpose of this study was to determine the effectiveness of the Youtube application as a means of learning sports for junior high school students during the pandemic. The results of this activity data show 52% of the students' basic volleyball knowledge pretest results were obtained. However, after giving the material with Youtube videos, the post-test results of knowledge increased to 84% so that learning through Youtube videos can improve student literacy. Therefore, there is a need for variations in learning methods during this pandemic which are expected to be able to improve the literacy quality of students.